CPT-TODIM method for interval neutrosophic MAGDM and its application to third-party logistics service providers selection - Zhang, Dan; Su, Yong; Zhao, Mengwei; Chen, Xudong (Technological and Economic Development of Economy, 2022)
The multiple attribute group decision making (MAGDM) has always been a concern in the research field. In this article, we establish the interval neutrosophic TODIM method based on cumulative prospect theory (CPT-IN-TODIM) for MAGDM issue. This new developed CPTIN-TODIM method has markedly superiority in describing decision maker’s psychological states, which utilizes the weight function to adjust weighting attributes distinguishing from the classical TODIM method. Then, this new developed method has been applied to select the third-party logistics service providers and been expound on the disparity with existing methods. Finally, the results of contrastive analysis indicate that this new developed method can lead to the appropriate conclusion and sticks out the differences between alternatives to provide clearer direction. Hence, the new developed CPT-IN-TODIM method is reliable and valid.First published online 19 November 2021